2019
DOI: 10.29173/istl3
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Digital Humanities and Applied Science Librarianship

Abstract: Awareness of faculty research interests is an important aspect of a subject librarian's responsibilities. This paper illustrates the potential of Voyant Tools, an application in wide use among digital humanities researchers, to reveal word patterns in the research output of applied science faculty. A corpus of recent article citations from Web of Science from two engineering departments was obtained, and the articles' title field was extracted and uploaded to the application. The exercise indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…However, the keyword cloud should be interpreted with caution, as it does not reflect any collocations, common occurrences or possible variations in meaning [93]. It would be more accurate to highlight the connections between the frequently occurring words with a link or a collocates graph [81,94]. In addition, some preliminary topics can be predicted, including online teaching skills, research skills, information and communication technology (ICT) (or digital) skills, and student learning.…”
Section: Needs Of and Barriers To Tpd (Qualitative Results)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the keyword cloud should be interpreted with caution, as it does not reflect any collocations, common occurrences or possible variations in meaning [93]. It would be more accurate to highlight the connections between the frequently occurring words with a link or a collocates graph [81,94]. In addition, some preliminary topics can be predicted, including online teaching skills, research skills, information and communication technology (ICT) (or digital) skills, and student learning.…”
Section: Needs Of and Barriers To Tpd (Qualitative Results)mentioning
confidence: 99%
“…Additionally, bubblelines and word trends were provided to help visualize the frequency and distribution of the five main keywords [79]. Lastly, close proximity links or collocates of the five main keywords are shown in order to visualize the underlying relationship within texts [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…A 21. század azonban jelentős változást hozott. A kutatás volumene, a publikált eredmények száma egy-egy szűkebb szakterületen is már-már áttekinthetetlenné vált, meghaladva a tízezer cikk/év értéket (Balkányi et al, 2021 stopwords lista), de mégis érdemes az alaphelyzeti stopword-listát kiegészíteni a szövegtestben még gyakran előforduló, de nem releváns szavakkal, betűsorokkal (Hendrigan, 2019). A példaként használt szövegtestből a VOYANT TOOLS program segítségével kinyert, "nyers" szakkifejezéslistából először készítettünk egy gyakorisági elemzést (terms frequency).…”
Section: Bevezetésunclassified
“…These results complement the studies of Gregory et al (2022) and Rambsy (2016) in which they concluded that Voyant Tools help them generate deeper understanding on their use cases. In a separate study, Hendrigan (2019) used Voyant Tools as a way to shed light and provide understanding on the different faculty research outputs of their department. Hendrigan concluded that the software is a viable heuristic approach to novices in digital humanities methods as it requires little steps to conduct analysis and requires no programming support in contrast to other existing software packages.…”
Section: Use Of Voyant Tools In Text Analysismentioning
confidence: 99%